Carbon pollution increases health inequities: lessons in resilience from the most vulnerable - Kristie L. Ebi; Stephen B. Fawcett; Jerry Spiegel; Horacio Tovalin
ABSTRACT Climate change is a social justice as well as an environmental issue. The magnitude and pattern of changes in weather and climate variables are creating differential exposures, vulnerabilities, and health risks that increase stress on health systems while exacerbating existing and creating new health inequities. Examples from national and local health adaptation projects highlight that developing partnerships across sectors and levels are critical for building climate-resilient health systems and communities. Strengthening current and implementing new health interventions, such as using environmental information to develop early warning systems, can be effective in protecting the most vulnerable. However, not all projected risks of climate change can be avoided by climate policies and programs, so health system strengthening is also critical. Applying a health inequity lens can reduce current vulnerabilities while building resilience to longer-term climate change. Taking inequities into account is critical if societies are to effectively prepare for and manage the challenges ahead.